2020
DOI: 10.5582/ddt.2020.03078
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with symptoms of depression among pregnant women with gestational diabetes mellitus in Japan

Abstract: gestational diabetes mellitus, depressive symptom, nutritionThe objective of this study was to explore the factors associated symptoms of depression among pregnant women with gestational diabetes mellitus (GDM) in Japan. This cross-sectional study was conducted at a hospital in Toyota, Japan, from January 2015 to June 2016. Pregnant women who visited the hospital and were diagnosed with GDM in the second trimester were enrolled. We analyzed depression symptoms using the Centers for Epidemiological Studies Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Indeed, dietary aspects and diet components (ex. vitamin D, folate, selenium intake, iron, vitamin B12, vitamin K, fiber intake, zinc) as well as diet-related inflammatory potential have been linked to depression outcomes [ 161 , 208 , 236 , 312 , 396 , 402 , 403 , 404 , 405 , 406 , 407 , 408 , 409 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 , 418 , 419 , 420 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 ]. A poor diet has been linked to depression through mechanisms such as inflammation [ 428 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, dietary aspects and diet components (ex. vitamin D, folate, selenium intake, iron, vitamin B12, vitamin K, fiber intake, zinc) as well as diet-related inflammatory potential have been linked to depression outcomes [ 161 , 208 , 236 , 312 , 396 , 402 , 403 , 404 , 405 , 406 , 407 , 408 , 409 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 , 418 , 419 , 420 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 ]. A poor diet has been linked to depression through mechanisms such as inflammation [ 428 ].…”
Section: Resultsmentioning
confidence: 99%
“…While screening with the Edinburgh Postnatal Depression Scale (EPDS) is suggested around the same time as the postpartum oGTT in the German guideline [11], screening during pregnancy is not implemented in the guideline, although there are several studies highlighting the association of GDM and depression not only after, but also before delivery. Recently, Hayashi et al could show heightened CES-D scores in women diagnosed with GDM [16], which was also found by Lee et al, who showed a high prevalence of anxious and depressive symptoms among patients with GDM [20]. Additionally, Pace et al found a nearly twofold increased risk of being diagnosed with depression during pregnancy in women with GDM [21].…”
Section: Discussionmentioning
confidence: 64%
“…In recently published studies, the results regarding the association of psychological abnormalities and BMI are inconsistent. While Hayashi et al could not find significant differences for depressive symptoms and maternal weight [16], Danyliv et al published a study where health-related quality of life was impaired by increased BMI and abnormal glucose tolerance after delivery [7]. In a qualitative study by Jarvie et al, it was shown through sequential in-depth interviews that women with a BMI above 30 kg/m 2 felt stigmatized by healthcare providers and perceived the needed lifestyle changes as unrealistic and counterproductive, especially when they were of low socioeconomic status [17].…”
Section: Discussionmentioning
confidence: 80%
“…Two longitudinal cohort studies assessing predictors of perinatal depressive symptoms among women with GDM in China suggested that hyperglycemia may be associated with perinatal depression 11,12 . A small cross‐sectional study in Japan also reported that symptoms of depression among pregnant women with GDM may be associated with diet 13 . Considering that concurrent diagnosis of GDM with antenatal depression is associated with higher rates of poor perinatal outcomes including preeclampsia, preterm birth and neonatal respiratory distress syndrome, 14,15 it is imperative that women who are most at risk of perinatal mental disorders are identified early and managed effectively.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 A small cross‐sectional study in Japan also reported that symptoms of depression among pregnant women with GDM may be associated with diet. 13 Considering that concurrent diagnosis of GDM with antenatal depression is associated with higher rates of poor perinatal outcomes including preeclampsia, preterm birth and neonatal respiratory distress syndrome, 14 , 15 it is imperative that women who are most at risk of perinatal mental disorders are identified early and managed effectively. In the New Zealand context, there are no data on predictors of perinatal mental disorders in women with GDM.…”
Section: Introductionmentioning
confidence: 99%